2007
DOI: 10.1029/2007jd008510
|View full text |Cite
|
Sign up to set email alerts
|

Doubled length of western European summer heat waves since 1880

Abstract: [1] We analyzed a new data set of 54 high-quality homogenized daily maximum temperature series from western Europe (Austria, Belgium, Croatia, Czech Republic, Denmark, Finland, France, Germany, Ireland, Netherlands, Portugal, Spain, Sweden, Switzerland, United Kingdom) to define more accurately the change in extreme warm Daily Summer Maximum Temperature (DSMT). Results from the daily temperature homogeneity analysis suggest that many instrumental measurements in the late 19th and early 20th centuries were warm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
329
3
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(375 citation statements)
references
References 38 publications
(113 reference statements)
26
329
3
6
Order By: Relevance
“…These findings suggest that moderate heat waves have increased in number and length from 1960, but any changes in the most extreme heat waves are unclear. These results are in qualitative agreement with other studies [5,7,13]. The stations with significant trends in heat wave numbers (Figure 2a) are spread around the UK.…”
Section: Trends In Heat Wavessupporting
confidence: 82%
See 2 more Smart Citations
“…These findings suggest that moderate heat waves have increased in number and length from 1960, but any changes in the most extreme heat waves are unclear. These results are in qualitative agreement with other studies [5,7,13]. The stations with significant trends in heat wave numbers (Figure 2a) are spread around the UK.…”
Section: Trends In Heat Wavessupporting
confidence: 82%
“…One study [13] stated that heat waves had become more frequent in May and June over the period 1878-2001, although it was unclear how this conclusion was reached. Another study [5] detected increases in the lengths of the longest heat waves in the CET over a similar period . It is clear from these studies that the full extent of trends in heat wave characteristics and their variations in the UK is not apparent and more investigation is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous observations-based studies have shown warming trends in both average temperatures [e.g., Vose et al, 2005aVose et al, , 2005bLawrimore et al, 2011] and temperature extremes . However, there is conflicting evidence -mostly based on regional analysis -as to whether the response in extremes is simply a result of a shifting mean [e.g., Griffiths et al, 2005;Simolo et al, 2011] or whether changes in other "higher order moments" of the daily temperature are also occurring [Della-Marta et al, 2007;Ballester et al, 2010]. Assessment of the probability distribution of daily temperatures for the globe would help address this question.…”
Section: Introductionmentioning
confidence: 99%
“…cold spells, frost days) have become less frequent (Klein Tank et al, 2002;Map 5.6). The average length of summer heat waves over Western Europe doubled over the period 1880 to 2005 and the frequency of hot days almost tripled (Della-Marta et al, 2007).…”
Section: Past Trendsmentioning
confidence: 99%